Akurasi Visual Proklamasi Kemerdekaan Republik Indonesia di Mata Chat GPT - Ambat, Yeremia Tulude; Khusyairi, Jhony Alfian; Arimbi, Diah Ariani (Universitas 17 Agustus 1945 Surabaya, 2025)
In today's era, Artificial Intelligence is increasingly entering into the layers of society, including the historical aspect. This study aims to analyze the accuracy of the illustration of the Proclamation of Indonesian Independence 1945 produced by ChatGPT using a qualitative research approach with Ferdinand de Saussure's semiotic analysis research method. This study found that the illustrations produced by AI were historically inaccurate, both in the depiction of the proclaimer, clothing, crowds, and main symbols such as the red and white flag. In addition, although some aspects, such as people's clothing, are close to the facts, most of the illustrations show deficiencies in conveying the true meaning of history. This distortion creates hyperreality, where the resulting visual elements reflect the algorithm's interpretation more than historical facts. This study also highlights that the inaccuracy is due to the limitations of AI in understanding cultural and historical contexts in depth. AI illustrations tend to function as symbolic metaphors rather than factual representations, obscuring the original meaning of events. That makes AI categorized as popular culture, which makes it inauthentic and unoriginal. It shows that AI still requires human intervention to ensure cultural and historical accuracy. This study concludes that the use of AI in representing historical events requires critical oversight to prevent the spread of biased or misleading information. The study emphasizes the need for collaboration between technology and human interpretation to maintain the accuracy of historical information.